Comparison of food intake in multiple sclerosis patients and healthy individuals – A hospital-based case-controlled study - Ghazavi, Yasaman; Bahadoran, Zahra; Nikfarjam, Mana; Beladi Moghaddam, Nahid; Mirmiran, Parvin; Haidari, Mohsen Reza (Iranian Journal of Child Neurology, 2019)
Objectives Nutritional factors affect the incidence, severity of symptoms and progression of multiple sclerosis (MS). However, the role of specific nutritional factors remains largely unknown in MS. We conducted this hospital-based case-controlled study to investigate the association between dietary intake and risk of MS. Methods: This study was conducted on 93 MS patients and 94 age-matched controls. MS was diagnosed based on 2010 McDonald criteria and Brain Magnetic Resonance Imaging. Dietary intake was assessed by using a validated semi-quantitative food frequency questionnaire. Odds ratio and 95% confidence interval of MS was calculated in different food item groups using multiple logistic regression models adjusted for potentially confounding variables and compared between the two groups. Results: There was no significant difference between age (34.62 ±9.68vs. 33.96±8.75) and BMI (23.96 ±4.07 vs. 24.47 ±4.07) of MS and control group respectively. Higher intake of processed meat (OR (95% CI)) = (2.07(1.18-3.63) and non-processed meat (1.38(1.13-1.68)) was found in the MS group compared with the control. Conclusion: Higher intake of processed meat and non-processed meat is associated with increased risk of MS. Further studies on the probable role of these nutritional factors in the pathogenesis of MS are suggested.